Method for preparing graphene nanosheets by using waste lithium battery negative electrode graphite ball milling and application of graphene nanosheets

Through ball milling technology, the graphene nanosheets are prepared from the negative electrode graphite of waste lithium batteries, which solves the problems of high cost and environmental pollution in the existing graphene preparation methods, and realizes the preparation of high-quality graphene and the low-carbon treatment of waste lithium batteries.

CN119683611AActive Publication Date: 2025-03-25CHIZHOU CN NEW MATERIALS & TECHNOLOGY CO LTD +2

Patent Information

Application Number
CN202510220547.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-03-25
Estimated Expiration
2045-02-27

AI Technical Summary

Technical Problem

The existing graphene preparation methods have high costs, complex processes and environmental pollution, which limit their large-scale applications.

Method used

Graphene nanosheets are prepared by ball milling the negative electrode of waste lithium batteries, and the combination of eutectic solvents and ultrasonic waves is used to achieve binder dissolution, peeling of metal impurities and protecting the graphite structure, avoiding the damage of strong acid/high temperature technical means.

Benefits of technology

High-quality graphene nanosheets were successfully prepared, with significantly improved performance and low-carbon treatment of waste lithium batteries, which was in line with the concept of green and low-carbon recycling.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium battery recovery, and particularly relates to a method for preparing graphene nanosheets by using waste lithium battery negative electrode graphite ball milling and application. Comprising the following steps: S1, immersing a graphite negative electrode block into a deep eutectic solvent, performing ultrasonic treatment under a constant temperature condition, filtering, washing with deionized water, and drying to obtain primarily treated graphite for later use; s2, putting the primarily treated graphite into a ball-milling tank, then adding a ball-milling medium and a stripping agent, and carrying out ball-milling treatment under the protection of inert gas; and S3, filtering the ball-milled product to obtain solid residues, washing the solid residues with deionized water until the solid residues are neutral, and drying the solid residues. The graphene nanosheet is successfully prepared by using the waste lithium battery negative electrode graphite as a raw material, so that on one hand, low-carbon treatment of the waste lithium battery is realized, and on the other hand, the successfully synthesized graphene nanosheet can be used as a high-added-value product to be widely applied to production of high-end products in the fields of electronics, building materials, biology and the like; and a green and low-carbon recovery concept is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium battery recycling, and specifically relates to a method for preparing graphene nanosheets by using graphite ball milling of waste lithium battery negative electrodes and its application. Background Art

[0002] Lithium batteries have the advantages of small size, high specific energy, low self-discharge, and no memory effect. They have become the most promising secondary battery and the fastest growing chemical energy storage power source. Due to the wide application of lithium batteries in energy storage systems such as portable communication devices, electric vehicles and ships, aerospace, and military fields, the lithium battery market is expanding. However, limited by a certain service life, the high demand in the lithium battery market will inevitably lead to a large number of waste lithium batteries. Waste lithium batteries contain harmful metals, flammable electrolytes, plastic shells, and a large amount of graphite materials. If they are not handled properly, they will not only cause serious environmental pollution and waste of resources, but also endanger human health. In addition, materials such as metals and graphite in waste lithium batteries also have important recycling value.

[0003] At present, the recycling of waste lithium batteries is mainly focused on the recovery of valuable metals in positive electrode materials. The main recycling methods are hydrometallurgy, dry metallurgy and bioleaching technology. With the continuous development of technology, the recycling of positive electrode materials has become quite mature and has formed an industrial chain. However, the recycling of waste lithium battery negative electrode materials cannot be ignored. In recent years, due to the advantages of low cost and high energy density, graphite materials have dominated the negative electrode materials of commercial lithium batteries. Globally, graphite accounts for 91% of the negative electrode materials of lithium batteries. On the one hand, graphite is used in large quantities in lithium batteries. Each kilowatt-hour battery requires about 1 kilogram of graphite, and a small and medium-sized electric vehicle requires up to 50 kilograms of graphite. Therefore, with the continuous development of the electric vehicle industry, the demand for graphite in the market has gradually increased. On the other hand, the graphite required for the negative electrode of lithium batteries has high requirements, and the purity should reach 99.5%, while graphite mines can usually only produce flake graphite with a purity of 90%-98%. In order to meet the requirements of battery-grade graphite, additional purification steps are required. Commonly used graphite purification methods are generally chemical methods and heat treatment methods, which not only increase the cost of graphite but also have high environmental hazards. Therefore, considering the expensive purification process, increasing demand and huge output of waste negative graphite, recycling negative graphite materials from waste lithium batteries is an effective way to obtain high-quality graphite. The recycling of negative graphite from waste lithium batteries has important practical significance for reducing the production cost of battery-grade graphite, avoiding environmental pollution and the sustainable development of the lithium battery industry.

[0004] As a two-dimensional material, graphene has great application potential in the fields of energy, electronics, biomedicine, etc. due to its excellent electrical, thermal, and mechanical properties. At present, the preparation methods of graphene mainly include mechanical exfoliation, chemical vapor deposition, redox method, etc. However, these methods generally have problems such as high cost, complex process, and environmental pollution, which limit the large-scale application of graphene.

[0005] Therefore, it is of great research significance to develop a method for preparing graphene nanosheets by ball milling graphite from the negative electrode of waste lithium batteries. Summary of the invention

[0006] The purpose of the present invention is to provide a method and application of preparing graphene nanosheets by using graphite ball milling of the negative electrode of waste lithium batteries in view of the existing problems.

[0007] The present invention is achieved through the following technical solutions: A method for preparing graphene nanosheets by ball milling graphite from the negative electrode of waste lithium batteries comprises the following steps: S1. Cut the graphite negative electrode sheet into 1×1 cm negative electrode blocks, immerse them in a low eutectic solvent, heat them in a water bath to 80-90°C, perform ultrasonic treatment for 4-5 hours at a constant temperature, filter them, rinse them with deionized water, and dry them in a drying oven for 24 hours to obtain the preliminarily treated graphite for use; S2, placing the preliminarily treated graphite in a ball milling tank, then adding ball milling media and a stripping agent, and performing ball milling treatment under the protection of an inert gas; S3. The ball-milled product is filtered to obtain a solid residue, which is washed with deionized water until neutral, and then placed in a vacuum drying oven at 60-70°C for drying.

[0008] Furthermore, the preparation method of the low eutectic solvent described in step S1 is: stirring the hydrogen bond acceptor and the hydrogen bond donor at a molar ratio of 1:2~4 at 80~100°C to form a transparent homogeneous liquid; after heating to 120~140°C, adding a functional additive to the transparent homogeneous liquid, and stirring at a constant temperature for 1~2h.

[0009] Furthermore, the hydrogen bond acceptor is one or more of choline chloride, betaine, and L-carnitine; The hydrogen bond donor is one or more of citric acid, tartaric acid and proline.

[0010] Furthermore, the added amount of the functional additive is 1-2wt%; The preparation of the functional additive comprises the following steps: (1) Ultrasonic dispersion of nano-silica in anhydrous ethanol, and after uniform ultrasonic dispersion, 10-18% of 3-aminopropyltriethoxysilane by mass of nano-silica is added, and the mixture is stirred at 60-70°C and 100-200 rpm for 3-5 hours to obtain pre-modified nano-silica for use; (2) Tocopherol and succinic anhydride are added into a three-necked flask at a molar ratio of 2-3:1, and then isobutyl acetate is added. After stirring to dissolve, the temperature is raised to 90-100°C, and 0.7-1% of the molar number of tocopherol is added with ethylenediamine. After constant temperature reaction for 2-3 hours, a tocopherol derivative is obtained for use; (3) Add 0.1-0.2 mmol of tocopherol derivative to MES buffer (4-morpholineethanesulfonic acid), stir to mix, then add 0.1-0.13 mmol of carbodiimide and 0.15-0.17 mmol of N-hydroxysuccinimide. Stir at 200-300 rpm for 20-30 min at room temperature, then add 0.5-1 times the amount of pre-modified nano-silica of the tocopherol derivative. Continue stirring for 10-12 h, centrifuge at 9000-10000 rpm for 10-15 min, collect the solid, wash with deionized water 3-5 times, place in a vacuum drying oven, and dry at 60-70 °C for 8-12 h.

[0011] Further, the ball milling medium in step S2 is a modified zirconia ball; The preparation method of the modified zirconia ball is: 1) Add 0.1 mol / L CaCl 2 , 0.05 mol / L sodium dihydrogen phosphate and 0.1 mg / mL mussel adhesion protein were prepared into a mineralization solution, and then zirconium oxide balls were added, stirred at 60-70°C and 200-300 rpm for 8-12 hours, and then filtered, and then dried to obtain mineralized zirconium oxide balls; 2) Use supersonic plasma spraying process to successively 2 O 3 -20% graphene, TiN-15% MoS 2 , nano-silicon dioxide is sprayed onto the surface of the mineralized zirconia ball, the spraying power is 80kW, Al 2 O 3 -20% graphene spraying thickness is 50~60μm, TiN-15MoS 2 The spraying thickness is 30~40μm, and the nano-silicon dioxide spraying thickness is 30~50μm.

[0012] Furthermore, the components and corresponding weight percentages of the stripping agent described in step S2 are: 1-butyl-3-methylimidazolium tetrafluoroborate 1-2%, 1-ethyl-3-methylimidazolium tetrafluoroborate 1-2%, urea 2-3%, and the balance is sodium dodecylbenzene sulfonate.

[0013] Furthermore, the ball milling speed in step S2 is 200-800 rpm, and the ball milling time is 8-12 h.

[0014] Furthermore, the inert gas described in step S2 is nitrogen or argon.

[0015] A graphene nanosheet prepared by the method described in any one of the above items.

[0016] An application of the graphene nanosheet as described above in silicone rubber modification.

[0017] Compared with the prior art, the present invention has the following advantages: The present invention successfully prepares graphene nanosheets using the negative electrode graphite of waste lithium batteries as raw materials. On the one hand, low-carbon treatment of waste lithium batteries is achieved. On the other hand, the successfully synthesized graphene nanosheets can be widely used as high-value-added products in the production of high-end products in multiple fields such as electronics, building materials, and biology, which is in line with the green and low-carbon recycling concept.

[0018] Firstly, the present invention performs an amino treatment on nano-silicon dioxide to change the surface charge of the nano-silicon dioxide and enhance its compatibility with tocopherol. Tocopherol reacts with succinic anhydride to generate a tocopherol derivative with a carboxylic acid group. The formed carboxylic acid group and the amino group form a covalent bond through carbodiimide-mediated condensation. The tocopherol is firmly anchored on the surface of the nano-silicon dioxide. The nano-silicon dioxide is added to a low eutectic solvent to improve the stability and viscosity of the solvent and inhibit metal corrosion. Under the coordinated action of the low eutectic solvent and ultrasound, the binder is dissolved, the metal impurities are stripped and the graphite structure is protected, thereby avoiding the damage problem of the current strong acid / high temperature technical means. In addition, the low eutectic solvent of the present invention can be recycled, thereby reducing the processing cost.

[0019] Secondly, the mineralizing liquid acts on the zirconia ball to generate a hydroxyapatite / Mfp-5 composite layer on the surface. The mussel protein combines with the zirconia surface through the catechol group to induce the directional growth of hydroxyapatite and form a bionic interface layer. Then, supersonic plasma spraying and multi-layer spraying are used to eliminate interface defects, improve fracture toughness, and improve ball milling effect. The ball milling medium and auxiliary stripping agent of the modified zirconia ball work synergistically. By optimizing the ball milling parameters, the friction force is increased, the interlayer force is reduced, and the stripping efficiency and quality are improved. The effective regulation of the size, number of layers and defects of graphene nanosheets is achieved. The prepared graphene nanosheets have a thinner layer structure, a more uniform size distribution and fewer defects, and the performance is significantly improved. DETAILED DESCRIPTION

[0020] In order to further explain the present invention, it is described below in conjunction with the following specific embodiments.

[0021] Example 1

[0022] A method for preparing graphene nanosheets by ball milling graphite from the negative electrode of waste lithium batteries comprises the following steps: S1. Cut the graphite negative electrode sheet into 1×1 cm negative electrode blocks, immerse them in a low eutectic solvent, heat them in a water bath to 80°C, perform ultrasonic treatment for 4 hours at a constant temperature, filter them, rinse them with deionized water, and dry them in a drying oven for 24 hours to obtain preliminarily treated graphite for use; The preparation method of the low eutectic solvent is as follows: betaine and citric acid are stirred at a molar ratio of 1:2 at 80° C. to form a transparent homogeneous liquid; after heating to 120° C., 1 wt % of a functional additive is added to the transparent homogeneous liquid, and stirred at a constant temperature for 1 hour; The preparation of the functional additive comprises the following steps: (1) Ultrasonic dispersion of nano-silica in anhydrous ethanol, and after uniform ultrasonic dispersion, 10% of the mass of nano-silica by 3-aminopropyltriethoxysilane was added, and the mixture was stirred at 60°C and 100 rpm for 3 h to obtain pre-modified nano-silica for use; (2) Tocopherol and succinic anhydride are added into a three-necked flask at a molar ratio of 2:1, and then isobutyl acetate is added. After stirring to dissolve, the temperature is raised to 90° C., and 0.7% of the molar amount of tocopherol is added with ethylenediamine. After the reaction is continued at a constant temperature for 2 hours, a tocopherol derivative is obtained for use; (3) Add 0.1 mmol of tocopherol derivative to MES buffer (4-morpholineethanesulfonic acid), stir and mix, then add 0.1 mmol of carbodiimide and 0.15 mmol of N-hydroxysuccinimide, stir at 200 rpm for 20 min, then add 0.5 times the amount of pre-modified nano-silica of tocopherol derivative, continue stirring for 10 h, centrifuge at 9000 rpm for 10 min, collect the solid, wash it with deionized water 3 times, place it in a vacuum drying oven, and dry it at 60 °C for 8 h; S2, placing the preliminarily treated graphite in a ball mill, then adding modified zirconia balls and a stripping agent, and ball milling under the protection of argon gas at 200 rpm for 8 hours; The preparation method of the modified zirconia ball is: 1) Add 0.1 mol / L CaCl 2 , 0.05 mol / L sodium dihydrogen phosphate and 0.1 mg / mL mussel adhesion protein were prepared into a mineralization solution, and then zirconium oxide balls were added, stirred at 60°C and 200 rpm for 8 hours, and then filtered, and then dried to obtain mineralized zirconium oxide balls; 2) Use supersonic plasma spraying process to successively 2 O 3 -20% graphene, TiN-15% MoS2 , nano-silicon dioxide is sprayed onto the surface of the mineralized zirconia ball, the spraying power is 80kW, Al 2 O 3 -20% graphene spraying thickness is 50μm, TiN-15MoS 2 The spraying thickness is 30μm, and the nano-silicon dioxide spraying thickness is 30μm; The components and corresponding weight percentages of the stripping agent are: 1-butyl-3-methylimidazolium tetrafluoroborate 1%, 1-ethyl-3-methylimidazolium tetrafluoroborate 1%, urea 2%, and the balance is sodium dodecylbenzene sulfonate; S3. The ball-milled product is filtered to obtain a solid residue, which is washed with deionized water until neutral, and then placed in a vacuum drying oven to dry at 60°C.

[0023] Example 2

[0024] A method for preparing graphene nanosheets by ball milling graphite from the negative electrode of waste lithium batteries comprises the following steps: S1. Cut the graphite negative electrode sheet into 1×1 cm negative electrode blocks, immerse them in a low eutectic solvent, heat them in a water bath to 85°C, perform ultrasonic treatment for 4.5 hours under constant temperature conditions, filter them, rinse them with deionized water, and dry them in a drying oven for 24 hours to obtain preliminarily treated graphite for use; The preparation method of the low eutectic solvent is as follows: betaine and citric acid are stirred at a molar ratio of 1:3 at 90° C. to form a transparent homogeneous liquid; after heating to 130° C., 1.5 wt % of a functional additive is added to the transparent homogeneous liquid, and stirred at a constant temperature for 1.5 hours; The preparation of the functional additive comprises the following steps: (1) Ultrasonic dispersion of nano-silica in anhydrous ethanol, and after uniform ultrasonic dispersion, 14% of 3-aminopropyltriethoxysilane by mass of nano-silica was added, and the mixture was stirred at 65° C. and 150 rpm for 4 h to obtain pre-modified nano-silica for use; (2) Tocopherol and succinic anhydride are added into a three-necked flask at a molar ratio of 2.5:1, and then isobutyl acetate is added. After stirring to dissolve, the temperature is raised to 95° C., and 0.85% of the molar number of tocopherol is added with ethylenediamine. After the reaction is continued at a constant temperature for 2.5 hours, a tocopherol derivative is obtained for use; (3) Add 0.15 mmol of tocopherol derivative to MES buffer (4-morpholineethanesulfonic acid), stir and mix, then add 0.12 mmol of carbodiimide and 0.16 mmol of N-hydroxysuccinimide, stir at 250 rpm for 25 min, then add 0.75 times of pre-modified nano-silica of tocopherol derivative, continue stirring for 11 h, centrifuge at 9500 rpm for 12.5 min, collect the solid, wash it with deionized water 4 times, place it in a vacuum drying oven, and dry it at 65 °C for 10 h; S2, placing the preliminarily treated graphite in a ball mill, then adding modified zirconia balls and a stripping agent, and ball milling under the protection of argon gas at 500 rpm for 10 hours; The preparation method of the modified zirconia ball is: 1) Add 0.1 mol / L CaCl 2 , 0.05 mol / L sodium dihydrogen phosphate and 0.1 mg / mL mussel adhesion protein were prepared into a mineralization solution, and then zirconium oxide balls were added, stirred at 65°C and 250 rpm for 10 hours, and then filtered, and then dried to obtain mineralized zirconium oxide balls; 2) Use supersonic plasma spraying process to successively 2 O 3 -20% graphene, TiN-15% MoS 2 , nano-silicon dioxide is sprayed onto the surface of the mineralized zirconia ball, the spraying power is 80kW, Al 2 O 3 -20% graphene spraying thickness is 55μm, TiN-15MoS 2 The spraying thickness is 35μm, and the nano-silicon dioxide spraying thickness is 40μm; The components and corresponding weight percentages of the stripping agent are: 1.5% 1-butyl-3-methylimidazolium tetrafluoroborate, 1.5% 1-ethyl-3-methylimidazolium tetrafluoroborate, 2.5% urea, and the balance is sodium dodecylbenzene sulfonate; S3. The ball-milled product is filtered to obtain a solid residue, which is washed with deionized water until neutral, and then placed in a vacuum drying oven at 65° C. for drying.

[0025] Example 3

[0026] A method for preparing graphene nanosheets by ball milling graphite from the negative electrode of waste lithium batteries comprises the following steps: S1. Cut the graphite negative electrode sheet into 1×1 cm negative electrode blocks, immerse them in a low eutectic solvent, heat them in a water bath to 90°C, perform ultrasonic treatment for 5 hours at a constant temperature, filter them, rinse them with deionized water, and dry them in a drying oven for 24 hours to obtain preliminarily treated graphite for use; The preparation method of the low eutectic solvent is as follows: betaine and citric acid are stirred at a molar ratio of 1:4 at 100° C. to form a transparent homogeneous liquid; after heating to 140° C., 2 wt % of a functional additive is added to the transparent homogeneous liquid, and stirred at a constant temperature for 2 hours; The preparation of the functional additive comprises the following steps: (1) Ultrasonic dispersion of nano-silica in anhydrous ethanol, and after uniform ultrasonic dispersion, 18% of 3-aminopropyltriethoxysilane by mass of nano-silica was added, and the mixture was stirred at 70°C and 200 rpm for 5 h to obtain pre-modified nano-silica for use; (2) Tocopherol and succinic anhydride are added into a three-necked flask at a molar ratio of 3:1, and then isobutyl acetate is added. After stirring to dissolve, the temperature is raised to 100° C., and ethylenediamine is added in an amount of 1% of the molar number of tocopherol. The tocopherol derivative is obtained after the reaction is kept at a constant temperature for 3 hours for use; (3) Add 0.2 mmol of tocopherol derivative to MES buffer (4-morpholineethanesulfonic acid), stir and mix, then add 0.13 mmol of carbodiimide and 0.17 mmol of N-hydroxysuccinimide, stir at 300 rpm for 30 min, then add 1 times the amount of pre-modified nano-silica of tocopherol derivative, continue stirring for 12 h, centrifuge at 10,000 rpm for 15 min, collect the solid, wash it with deionized water 5 times, place it in a vacuum drying oven, and dry it at 70 °C for 12 h; S2, placing the preliminarily treated graphite in a ball mill, then adding modified zirconia balls and a stripping agent, and ball milling under the protection of argon gas at 800 rpm for 12 hours; The preparation method of the modified zirconia ball is: 1) Add 0.1 mol / L CaCl 2 , 0.05 mol / L sodium dihydrogen phosphate and 0.1 mg / mL mussel adhesion protein were prepared into a mineralization solution, and then zirconium oxide balls were added, stirred at 70°C and 300 rpm for 12 hours, and then filtered, and then dried to obtain mineralized zirconium oxide balls; 2) Use supersonic plasma spraying process to successively 2 O 3 -20% graphene, TiN-15% MoS 2 , nano-silicon dioxide is sprayed onto the surface of the mineralized zirconia ball, the spraying power is 80kW, Al 2 O 3 -20% graphene spraying thickness is 60μm, TiN-15MoS 2 The spraying thickness is 40μm, and the nano-silicon dioxide spraying thickness is 50μm; The components and corresponding weight percentages of the stripping agent are: 2% 1-butyl-3-methylimidazolium tetrafluoroborate, 2% 1-ethyl-3-methylimidazolium tetrafluoroborate, 3% urea, and the balance is sodium dodecylbenzene sulfonate; S3. The ball-milled product is filtered to obtain a solid residue, which is washed with deionized water until neutral, and then placed in a vacuum drying oven to dry at 70°C.

[0027] Comparative Example 1 A method for preparing graphene nanosheets by ball milling graphite from the negative electrode of waste lithium batteries comprises the following steps: S1. Cut the graphite negative electrode sheet into 1×1 cm negative electrode blocks, immerse them in a low eutectic solvent, heat them in a water bath to 85°C, perform ultrasonic treatment for 4.5 hours under constant temperature conditions, filter them, rinse them with deionized water, and dry them in a drying oven for 24 hours to obtain preliminarily treated graphite for use; The preparation method of the low eutectic solvent is as follows: betaine and citric acid are stirred at a molar ratio of 1:3 at 90° C. to form a transparent homogeneous liquid; S2, placing the preliminarily treated graphite in a ball mill, then adding modified zirconia balls and a stripping agent, and ball milling under the protection of argon gas at 500 rpm for 10 hours; The preparation method of the modified zirconia ball is: 1) Add 0.1 mol / L CaCl 2 , 0.05 mol / L sodium dihydrogen phosphate and 0.1 mg / mL mussel adhesion protein were prepared into a mineralization solution, and then zirconium oxide balls were added, stirred at 65°C and 250 rpm for 10 hours, and then filtered, and then dried to obtain mineralized zirconium oxide balls; 2) Use supersonic plasma spraying process to successively 2 O 3 -20% graphene, TiN-15% MoS 2 , nano-silicon dioxide is sprayed onto the surface of the mineralized zirconia ball, the spraying power is 80kW, Al 2 O 3 -20% graphene spraying thickness is 55μm, TiN-15MoS 2 The spraying thickness is 35μm, and the nano-silicon dioxide spraying thickness is 40μm; The components and corresponding weight percentages of the stripping agent are: 1.5% 1-butyl-3-methylimidazolium tetrafluoroborate, 1.5% 1-ethyl-3-methylimidazolium tetrafluoroborate, 2.5% urea, and the balance is sodium dodecylbenzene sulfonate; S3. The ball-milled product is filtered to obtain a solid residue, which is washed with deionized water until neutral, and then placed in a vacuum drying oven at 65° C. for drying.

[0028] Comparative Example 2 A method for preparing graphene nanosheets by ball milling graphite from the negative electrode of waste lithium batteries comprises the following steps: S1. Cut the graphite negative electrode sheet into 1×1 cm negative electrode blocks, immerse them in a low eutectic solvent, heat them in a water bath to 85°C, perform ultrasonic treatment for 4.5 hours under constant temperature conditions, filter them, rinse them with deionized water, and dry them in a drying oven for 24 hours to obtain preliminarily treated graphite for use; The preparation method of the low eutectic solvent is as follows: betaine and citric acid are stirred at a molar ratio of 1:3 at 90° C. to form a transparent homogeneous liquid; after heating to 130° C., 1.5 wt % of a functional additive is added to the transparent homogeneous liquid, and stirred at a constant temperature for 1.5 hours; The preparation of the functional additive comprises the following steps: (1) Ultrasonic dispersion of nano-silica in anhydrous ethanol, and after uniform ultrasonic dispersion, 14% of 3-aminopropyltriethoxysilane by mass of nano-silica was added, and the mixture was stirred at 65° C. and 150 rpm for 4 h to obtain pre-modified nano-silica for use; (2) Tocopherol and succinic anhydride are added into a three-necked flask at a molar ratio of 2.5:1, and then isobutyl acetate is added. After stirring to dissolve, the temperature is raised to 95° C., and 0.85% of the molar number of tocopherol is added with ethylenediamine. After the reaction is continued at a constant temperature for 2.5 hours, a tocopherol derivative is obtained for use; (3) Add 0.15 mmol of tocopherol derivative to MES buffer (4-morpholineethanesulfonic acid), stir and mix, then add 0.12 mmol of carbodiimide and 0.16 mmol of N-hydroxysuccinimide, stir at 250 rpm for 25 min, then add 0.75 times of pre-modified nano-silica of tocopherol derivative, continue stirring for 11 h, centrifuge at 9500 rpm for 12.5 min, collect the solid, wash it with deionized water 4 times, place it in a vacuum drying oven, and dry it at 65 °C for 10 h; S2, placing the preliminarily treated graphite in a ball mill, then adding zirconium oxide balls and a stripping agent, and ball milling under the protection of argon gas at 500 rpm for 10 hours; The components and corresponding weight percentages of the stripping agent are: 1.5% 1-butyl-3-methylimidazolium tetrafluoroborate, 1.5% 1-ethyl-3-methylimidazolium tetrafluoroborate, 2.5% urea, and the balance is sodium dodecylbenzene sulfonate; S3. The ball-milled product is filtered to obtain a solid residue, which is washed with deionized water until neutral, and then placed in a vacuum drying oven at 65° C. for drying.

[0029] Comparative Example 3 A method for preparing graphene nanosheets by ball milling graphite from the negative electrode of waste lithium batteries comprises the following steps: S1. Cut the graphite negative electrode sheet into 1×1 cm negative electrode blocks, immerse them in a low eutectic solvent, heat them in a water bath to 85°C, perform ultrasonic treatment for 4.5 hours under constant temperature conditions, filter them, rinse them with deionized water, and dry them in a drying oven for 24 hours to obtain preliminarily treated graphite for use; The preparation method of the low eutectic solvent is as follows: betaine and citric acid are stirred at a molar ratio of 1:3 at 90° C. to form a transparent homogeneous liquid; after heating to 130° C., 1.5 wt % of a functional additive is added to the transparent homogeneous liquid, and stirred at a constant temperature for 1.5 hours; The preparation of the functional additive comprises the following steps: (1) Ultrasonic dispersion of nano-silica in anhydrous ethanol, and after uniform ultrasonic dispersion, 14% of 3-aminopropyltriethoxysilane by mass of nano-silica was added, and the mixture was stirred at 65° C. and 150 rpm for 4 h to obtain pre-modified nano-silica for use; (2) Tocopherol and succinic anhydride are added into a three-necked flask at a molar ratio of 2.5:1, and then isobutyl acetate is added. After stirring to dissolve, the temperature is raised to 95° C., and 0.85% of the molar number of tocopherol is added with ethylenediamine. After the reaction is continued at a constant temperature for 2.5 hours, a tocopherol derivative is obtained for use; (3) Add 0.15 mmol of tocopherol derivative to MES buffer (4-morpholineethanesulfonic acid), stir and mix, then add 0.12 mmol of carbodiimide and 0.16 mmol of N-hydroxysuccinimide, stir at 250 rpm for 25 min, then add 0.75 times of pre-modified nano-silica of tocopherol derivative, continue stirring for 11 h, centrifuge at 9500 rpm for 12.5 min, collect the solid, wash it with deionized water 4 times, place it in a vacuum drying oven, and dry it at 65 °C for 10 h; S2, placing the preliminarily treated graphite in a ball milling jar, then adding modified zirconium oxide balls and ball milling under the protection of argon gas, ball milling at 500 rpm for 10 hours; The preparation method of the modified zirconia ball is: 1) Add 0.1 mol / L CaCl 2 , 0.05 mol / L sodium dihydrogen phosphate and 0.1 mg / mL mussel adhesion protein were prepared into a mineralization solution, and then zirconium oxide balls were added, stirred at 65°C and 250 rpm for 10 hours, and then filtered, and then dried to obtain mineralized zirconium oxide balls; 2) Use supersonic plasma spraying process to successively 2 O 3 -20% graphene, TiN-15% MoS 2, nano-silicon dioxide is sprayed onto the surface of the mineralized zirconia ball, the spraying power is 80kW, Al 2 O 3 -20% graphene spraying thickness is 55μm, TiN-15MoS 2 The spraying thickness is 35μm, and the nano-silicon dioxide spraying thickness is 40μm; S3. The ball-milled product is filtered to obtain a solid residue, which is washed with deionized water until neutral, and then placed in a vacuum drying oven at 65° C. for drying.

[0030] Performance Testing The graphene nanosheets obtained in each implementation and comparative example were applied to the modification of silicone rubber materials. The graphene nanosheets and the silicone rubber raw materials were uniformly mixed using a double-roll open mill. The mixing temperature was 40° C., the mixing time was 90 min, and the mixing amount of the graphene nanosheets was 1.0 wt % to obtain graphene-modified silicone.

[0031] Then, a laser thermal conductivity meter was used to test the thermal diffusion coefficient and thermal conductivity of the common silica gel and the graphene-modified silica gel obtained by the present invention by using a laser flash method. The test results are shown in Table 1 below.

[0032] Table 1 <![CDATA[Thermal diffusivity mm 2 / s]]> Thermal conductivity W / (m·K) Ordinary silicone rubber 0.149 0.141 Example 1 1.353 1.682 Example 2 1.365 1.683 Example 3 1.364 1.679 Comparative Example 1 1.186 1.226 Comparative Example 2 1.152 1.407 Comparative Example 3 1.290 1.482 It can be seen from Table 1 above that applying the graphene nanosheets prepared by the method of the present invention to silicone rubber materials can significantly improve the thermal diffusion coefficient and thermal conductivity of silicone rubber.

[0033] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing graphene nanosheets by using graphite ball milling of waste lithium battery negative electrode, characterized in that: The steps include: S1. Cut the graphite negative electrode sheet into 1×1 cm negative electrode blocks, immerse them in a low eutectic solvent, heat them in a water bath to 80-90°C, perform ultrasonic treatment for 4-5 hours at a constant temperature, filter them, rinse them with deionized water, and dry them in a drying oven for 24 hours to obtain the preliminarily treated graphite for use; S2, placing the preliminarily treated graphite in a ball milling tank, then adding ball milling media and a stripping agent, and performing ball milling treatment under the protection of an inert gas; S3. The ball-milled product is filtered to obtain a solid residue, which is washed with deionized water until neutral, and then placed in a vacuum drying oven at 60-70°C for drying.

2. A method for preparing graphene nanosheets by using graphite ball milling of the negative electrode of waste lithium batteries according to claim 1, characterized in that: The preparation method of the low eutectic solvent described in step S1 is: stirring the hydrogen bond acceptor and the hydrogen bond donor at a molar ratio of 1:2~4 at 80~100°C to form a transparent homogeneous liquid; after heating to 120~140°C, adding a functional additive to the transparent homogeneous liquid, and stirring at a constant temperature for 1~2h.

3. A method for preparing graphene nanosheets by using graphite ball milling of the negative electrode of waste lithium batteries according to claim 2, characterized in that: The hydrogen bond acceptor is one or more of choline chloride, betaine, and L-carnitine; The hydrogen bond donor is one or more of citric acid, tartaric acid and proline.

4. A method for preparing graphene nanosheets by using graphite ball milling of the negative electrode of waste lithium batteries according to claim 2, characterized in that: The added amount of the functional additive is 1~2wt%; The preparation of the functional additive comprises the following steps: (1) Ultrasonic dispersion of nano-silica in anhydrous ethanol, and after uniform ultrasonic dispersion, 10-18% of 3-aminopropyltriethoxysilane by mass of nano-silica is added, and the mixture is stirred at 60-70°C and 100-200 rpm for 3-5 hours to obtain pre-modified nano-silica for use; (2) Tocopherol and succinic anhydride are added into a three-necked flask at a molar ratio of 2-3:1, and then isobutyl acetate is added. After stirring to dissolve, the temperature is raised to 90-100°C, and 0.7-1% of the molar number of tocopherol is added with ethylenediamine. After constant temperature reaction for 2-3 hours, a tocopherol derivative is obtained for use; (3) Add 0.1-0.2 mmol of tocopherol derivative to MES buffer, stir to mix, then add 0.1-0.13 mmol of carbodiimide and 0.15-0.17 mmol of N-hydroxysuccinimide. Stir at 200-300 rpm for 20-30 min at room temperature, then add 0.5-1 times the amount of pre-modified nano-silica of tocopherol derivative. Continue stirring for 10-12 h, centrifuge at 9000-10000 rpm for 10-15 min, collect the solid, wash with deionized water for 3-5 times, place in a vacuum drying oven, and dry at 60-70 °C for 8-12 h.

5. The method for preparing graphene nanosheets by using graphite ball milling of the negative electrode of waste lithium batteries according to claim 1, characterized in that: The ball milling medium described in step S2 is a modified zirconia ball; The preparation method of the modified zirconia ball is: 1) 0.1 mol / L CaCl2, 0.05 mol / L sodium dihydrogen phosphate and 0.1 mg / mL mussel adhesion protein were prepared into a mineralization solution, and then zirconium oxide balls were added, stirred at 60-70°C and 200-300 rpm for 8-12 hours, filtered, and then dried to obtain mineralized zirconium oxide balls; 2) The supersonic plasma spraying process is used to spray nano-Al2O3-20% graphene, TiN-15%MoS2, and nano-silicon dioxide onto the surface of the mineralized zirconia ball in sequence. The spraying power is 80kW, the Al2O3-20% graphene spraying thickness is 50~60μm, the TiN-15MoS2 spraying thickness is 30~40μm, and the nano-silicon dioxide spraying thickness is 30~50μm.

6. The method for preparing graphene nanosheets by using graphite ball milling of the negative electrode of waste lithium batteries according to claim 1, characterized in that: The components and corresponding weight percentages of the stripping agent in step S2 are: 1-butyl-3-methylimidazolium tetrafluoroborate 1-2%, 1-ethyl-3-methylimidazolium tetrafluoroborate 1-2%, urea 2-3%, and the balance is sodium dodecylbenzene sulfonate.

7. The method for preparing graphene nanosheets by using graphite ball milling of the negative electrode of waste lithium batteries according to claim 1, characterized in that: The ball milling speed described in step S2 is 200-800 rpm, and the ball milling time is 8-12 h.

8. The method for preparing graphene nanosheets by ball milling of graphite from the negative electrode of waste lithium batteries according to claim 1, characterized in that: The inert gas described in step S2 is nitrogen or argon.

9. The graphene nanosheet prepared by the method according to any one of claims 1 to 8.

10. Use of the graphene nanosheets as claimed in claim 9 in silicone rubber modification.

Citation Information

Patent Citations

  • Method for preparing graphene or graphene oxide by using high-efficiency and low-cost mechanical stripping

    CN101817516A

  • Nitrogen-doped graphene nanobelt and preparation method thereof

    CN103833021A

  • Method for preparing graphene by recovering graphite from waste lithium ion battery negative electrode material

    CN111384462A

  • Method for preparing graphene nanosheets by using waste lithium battery negative electrode graphite ball milling and application of graphene nanosheets

    CN115650216A

  • Regeneration method of waste graphite of retired lithium battery, regenerated graphite and application of regenerated graphite

    CN118529726A

Cited By

  • Method for preparing graphene by plasma-assisted ball milling

    CN120534963A

  • A method for preparing graphene by plasma-assisted ball milling

    CN120534963B